Radiology outcome of gradual increase in skeletal traction in a acetabular fracture - Mohd Shukri Omar (Kulliyyah of Medicine, International Islamic University Malaysia, 2018)
This study was designed to evaluate the effect of gradual increment of vector traction weight towards reducing displaced acetabular fracture preoperatively. This is a prospective study conducted at Hospital Tuanku Jaafar, Seremban between June 2016 until December 2017. A total of 21 patients were included in the study. Patients were put on supracondylar and lateral traction in which reduction effects were assessed by serial radiographs. Displaced acetabular fracture was defined radiologically as displacement of both ileopectinial and ileoischial line of more than 2cm. Male gender predominant (82,1%) and majority caused by road traffic accident (75.0%). Majority are bicolumnar type (46.4%) followed by T-type acetabular fracture (25.0%). Reduction achieved in 18 cases. Traction weight ranges from 5% to 33.33% (median, 20%) of body weight required for fracture reduction. Only 4 (19%) require 10% or less body weight traction for reduction while majority require higher traction weight. 10 patients (47.6%) require between 16% to 24% body weight traction for fracture reduction. Median of 200gm/kg traction weight (range, 50gm to 333gm) are required for fracture reduction (p=0.740). All (57.14%) patients applied with traction within 7 days of trauma achieved reduction. Traction applied within 7 days of trauma significantly affect preoperative fracture reduction (p=0.025). Complication rate are 17.9% comprising of pain and pin-tract infection. Weight (p=0.687) and period of traction application (p=1.00) did not affect development of complications. Vector traction of around 20% body weight (200mg/kg) reduce displaced acetabular fracture preoperatively. Delay in traction application more than 7 days significantly affect preoperative fracture reduction. Abbreviation: acetabular fracture, complications, vector traction, preoperative traction, traction weight